2019
DOI: 10.1097/mpg.0000000000002224
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Lysosomal Acid Lipase Deficiency in Children With Unexplained Liver Disease

Abstract: Objectives: Evidence suggests that lysosomal acid lipase deficiency (LAL-D) is often underdiagnosed because symptoms may be nonspecific. We aimed to investigate the prevalence of LAL-D in children with unexplained liver disease and to identify demographic and clinical features with a prospective, multicenter, cross-sectional study. Methods: Patients (aged 3 months–18 years) who had unexplained transaminase elevation, unexplained hepatomegaly or hepatosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…At the end of the selection process, only 108 articles were retained. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , …”
Section: Resultsunclassified
“…At the end of the selection process, only 108 articles were retained. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , …”
Section: Resultsunclassified
“…Nobody was enzyme deficient. It was reported that the enzyme activity between 0.15 -0.40 nmol/punch/hour could be related with LIPA gene heterozygous carriers [10]. But on the other hand, it was underlined that it was not reliable approach to identify the carriers [11].…”
Section: Discussionmentioning
confidence: 99%
“…One study screening for LALD based on clinical suspicion (hepatomegaly, a 1.5-fold increase in transaminases compared to reference limits, or dyslipidemia with or without splenomegaly, gastrointestinal dysfunction, or liver steatosis, fibrosis, or cirrhosis) successfully identified 19 cases in 4,174 using DBS ( Tebani et al, 2021 ). Another study screening 810 children in Turkey with either elevated transaminases for 3 months, hepatomegaly, or liver steatosis, fibrosis, or cirrhosis not explained by obesity or other causes by DBS found two LALD patients ( Kuloglu et al, 2019 ). A recent study published in this series of Frontiers in Genetics screened 669 Slovenian children with familial hypercholesterolemia and detected 3 cases of LALD homozygous for c.894G>A ( Sustar et al, 2022 ).…”
Section: Lal Deficiency States–wolman Disease and Cesdmentioning
confidence: 99%